Fraud against European Public Funds - Quirke, Brendan (Crime, law and social change, 1999)
This article considers the approach adopted towards the fight against fraud within the European Union. It considers the role(s) of the various agencies at both a transnational and national level. It concludes that it is impossible to effectively fight transnational fraud across fifteen different legal systems. There is an urgent need for the "Corpus Juris" proposals to be adopted so that a defined European legal space can be created which is able to deal with crimes against the European budget.